2012
DOI: 10.1136/acupmed-2011-010034
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Chemotherapy-Induced Peripheral Neuropathy (Cipn): A Pilot Study Using Neurography

Abstract: Objectives Chemotherapy-induced peripheral neuropathy (CIPN) can produce severe neurological defi cits and neuropathic pain and is a potential reason for terminating or suspending chemotherapy treatments. Specifi c and effective curative treatments are lacking. Methods A pilot study was conducted to evaluate the therapeutic effect of acupuncture on CIPN as measured by changes in nerve conduction studies (NCS) in six patients treated with acupuncture for 10 weeks in addition to best medical care and fi ve contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 14 publications
3
68
1
Order By: Relevance
“…On the basis of promising findings from earlier studies [19-25,27,28,32], we designed the current trial to evaluate the feasibility, safety, and initial efficacy of acupuncture for the treatment of thalidomide- and/or bortezomib-induced chronic PN in patients with MM. Results from this study will help inform the design of a future, large randomized clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of promising findings from earlier studies [19-25,27,28,32], we designed the current trial to evaluate the feasibility, safety, and initial efficacy of acupuncture for the treatment of thalidomide- and/or bortezomib-induced chronic PN in patients with MM. Results from this study will help inform the design of a future, large randomized clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, TCM is regarded as a complementary therapy to cancer patients worldwide [5-7]. A number of literatures have reported that acupoint stimulation may be effective on symptom management [8,9], reduction of chemotherapy-induced side effects [10-12], and quality of life improvement [13] in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as research continues into the role of pharmacological agents for treatment and/or prevention of oxaliplatin-induced peripheral neuropathy; interest in nonpharmacological treatment options is increasing. Studies have been lacking on non-pharmacological therapy for the treatment of oxaliplatin-peripheral neuropathy, although some clinical studies have been performed on acupuncture for the treatment of chemotherapy-induced peripheral neuropathy [39][40][41][42]. These studies reported improvements following acupuncture in the Visual Analog System (VAS) pain scale, gait, and nerve conduction tests, and reduced use of pain medication.…”
Section: Discussionmentioning
confidence: 96%